Murabahah dalam Literatur Fikih Klasik dan Kontemporer - Permana, Toni; Muradi, Fran Evan Cahyo (Fakultas Syariah IAIN Kerinci, 2022)
Along with the development of the times, of course, the problems and phenomena of this muamalah are increasingly diverse, so that it requires deeper study. The scholars found a solution to the muamalah phenomenon which became known as the contemporary concept of muamalah fiqh, where the concept is very different from the classical muamalah fiqh concept. Discussion regarding the two opinions regarding the murabaha concept needs to be understood more deeply for practitioners and academics in developing products sharia financial institution. Therefore the purpose of this discussion is to find out comparatively the concept of murabaha according to classical and contemporary studies as well as the weaknesses and strengths of the concept. This research is a library research (library research) with a qualitative descriptive model with a focus on studies on various matters relating to the classic murabaha buying and selling system in muamalah or business studies from the point of view of experts and the contemporary murabaha buying and selling system in the banking system. The results of this study indicate that the concept of murabaha according to classical fiqh is the concept of buying and selling a product purely for the purpose of trading that upholds the value of trust and cannot be fully implemented in today's banking world. While the advantages of the murabaha concept in contemporary fiqh studies are that it is a short-term investment mechanism that is quite easy and the weaknesses of murabaha in contemporary fiqh studies can be seen from the majority of mechanisms in Islamic banking that take too much into account the loss/risk of goods that are not in accordance with the customer's wishes.